Utilization of 3D Animation Technology in Subak Preservation: Maintaining Social Balance in Balinese Cultural Heritage - Bramayudha, I Gede; Agustini, Ketut; Mertayasa, I Nengah Eka; Jajuri, Titiyaka Binti; Edwards, Joseph (Program Magister Teknologi Pendidikan Universitas Jambi, 2025)
Subak, a traditional Balinese irrigation system, is an agricultural management method and a cultural heritage embodying the Tri Hita Karana philosophy, which emphasizes harmony between humans, nature, and the divine. However, modern challenges such as land-use changes, urbanization, and declining agricultural engagement among younger generations threaten its sustainability. This study aims to develop a 3D animated film as an educational tool to enhance public understanding of pawongan, the social aspect of subak, through digital media. The research follows the Multimedia Development Life Cycle (MDLC) method for animation production and a quasi-experimental design with pre-test and post-test evaluations to measure its effectiveness. Data analysis includes paired sample t-tests to assess comprehension improvements and qualitative analysis from interviews and observations. Results show that the experimental group, which watched the animation, demonstrated a significantly higher understanding of pawongan than the control group, which received conventional education methods. Furthermore, audience engagement and discussions post-viewing suggest that digital media fosters a stronger emotional connection and motivation for cultural preservation. This study highlights the novel use of 3D animation as an effective medium for cultural education, bridging the gap between traditional knowledge and digital learning. Future research should explore interactive applications, such as augmented reality (AR) or gamification, to enhance public engagement and long-term impact on subak preservation.